(untitled) (Research, Society and Development, 2020)
Trinexapac-ethyl spraying time and proper nitrogen rate are essential to reduce plant height and lodging at harvest, without affecting rice yield and nutritional balance. This study aimed to evaluate trinexapac-ethyl spraying time and N contents as topdressing for upland rice paddies. The experiment was carried out in a randomized block design and a 4x5 factorial scheme, with four replications. Treatments consisted of four trinexapac-ethyl spraying times, in the phenological stages of tillering, floral differentiation, between tillering and floral differentiation, and a control (without spraying), and five nitrogen rates (0, 50, 100, 150, and 200, kg ha-1) as topdressing. As nitrogen topdressing rates increased, leaf contents of N, Fe++, and Zn++ increased, while S and Mn++ decreased; however, contents of P, Ca++, Mg++, B, and Cu++ were little influenced. When trinexapac-ethyl was applied, leaf contents of N, P, S, B, and Zn++ were little influenced, while P, Ca++, Mg++, Fe++, and Mn++ increased, and Cu++ decreased. Trinexapac-ethyl can be applied at tillering without decreasing rice yield. Upland rice increased grain yield by 58 and 46% in two consecutive crop years due to application of about 120 kg N ha-1 as topdressing.